Metacommunication as second order communication - Mateus, Samuel (2017)
By giving full emphasis to the impossibility of not to communicate, the first axiom of communication stresses how communication is an event not subject to cessation. It is this never-ending characteristic that impels us to the need to ponder on metacommunication as “communication about communication”. By taking a philosophically informed and pragmatic stance, this paper deals with the concept of “metacommunication” and tries to incorporate it in the theory of communication. It posits communication is a multilevel dialectical happening in which metacommunication presents itself a kind of second order communication. The paper describes communication as an ad infinitum process in which every communication supposes always more communication. Metacommunication is the answer to the relationship level of communication and that’s why we postulate metacommunication as a re-communicating communication.